2015
DOI: 10.1002/cbic.201500310
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants for Protein Stabilization by Insertional Fusion to a Thermophilic Host Protein

Abstract: A universal method that improves protein stability and evolution has thus far eluded discovery. Recently, however, studies have shown that insertional fusion to a protein chaperone stabilized various target proteins with minimal negative effects. The improved stability was derived from insertion into a hyperthermophilic protein, Pyrococcus furiosus maltodextrin-binding protein (PfMBP), rather than from changes to the target protein sequence. In this report, by evaluating the thermodynamic and kinetic stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…These characteristics show the pH and temperature compatibility of XBP with the xylanase domain, and in addition suggest a possible thermal stabilization of the catalytic domain by the fusion with XBP. Recent studies show that the insertion of a less stable domain in a more thermostable domain may be an important strategy to increase the thermostability of the less stable protein [ 19 22 ]. Furthermore, it is noteworthy that the fusion with XBP involves both the N- and C-terminal regions of the xylanase, and alterations in both these regions are known to influence thermostability of the XynA [ 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…These characteristics show the pH and temperature compatibility of XBP with the xylanase domain, and in addition suggest a possible thermal stabilization of the catalytic domain by the fusion with XBP. Recent studies show that the insertion of a less stable domain in a more thermostable domain may be an important strategy to increase the thermostability of the less stable protein [ 19 22 ]. Furthermore, it is noteworthy that the fusion with XBP involves both the N- and C-terminal regions of the xylanase, and alterations in both these regions are known to influence thermostability of the XynA [ 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…More recently, a series of studies performed by Kim and coworkers demonstrated that domain insertion of a guest protein may benefit from high thermostability of a host protein [38,39,40,41]. Insertional fusion has recently been highlighted as a novel means of creating multi-domain protein complexes, where functionalities are often integrated and coupled with each other.…”
Section: Thermophilic Proteins As a Scaffold For Functional Evolutionmentioning
confidence: 99%
“…To overcome such energetic penalty, Kim and coworkers used a thermophilic maltodextrin-binding protein from Pyrococcus furiosus as a host protein, into which various guest enzyme domains, such as exoinulinase, TEM-1 β-lactamase and xylanase, were successfully inserted. The insertional fusions led to the creation of chimeric protein complexes, where thermostability of guest enzyme domains was improved by various mechanisms [38,39,40,41,42]. In contrast, similar insertional fusion into a mesophilic maltodextrin-binding protein from E. coli lowered thermostability and expression levels of a guest enzyme domain [39].…”
Section: Thermophilic Proteins As a Scaffold For Functional Evolutionmentioning
confidence: 99%
“…Furthermore, different from end-to-end fusion in which domains are linked by a single contact point, when two domains are fused by domain insertion, they are linked by peptidyl bonds at two contact points with more intimate connection between the two proteins. This double contact can increase the protein stability of generated chimeras [23, 35, 40, 41], and the intimate connection can be used to couple the functions of two fused proteins.…”
Section: Engineering Switches By Protein Domain Insertionmentioning
confidence: 99%